Assessing Emotional Intelligence and Workplace Support for Achieving Optimal Job Satisfaction - Muzakki, Muzakki; Yudistira, Dewangga; Maulifa, Nur Alif (Telaah Bisnis, 2024)
This study investigates the influence of emotional intelligence, colleagues’ support, and support from supervisors on job satisfaction among teachers of Wachid Hasyim Vocational School and High School in Surabaya. Using the purposive sampling technique, 48 teachers were sampled in this study, and the data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The findings of this study demonstrate that emotional intelligence has a significant influence on job satisfaction, emphasizing the importance of emotional ability in increasing teachers' job satisfaction. Conversely, although the support from colleagues and supervisors also showed positive effects, the effect on job satisfaction was not statistically significant. The practical implications of these results highlight the need for additional focus on developing social support in the workplace to further improve job satisfaction, with recommendations for schools to scale up peer and employer support initiatives to create a more fulfilling work environment for teachers.